1991
DOI: 10.1002/j.0022-0337.1991.55.9.tb02570.x
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the dental care management of patients with bloodborne infectious diseases: an opinion survey of dental school seniors

Abstract: This study revealed some significant findings concerning the views of dental school seniors. Through a series of questions, we determined the opinions that seniors had about treating patients with bloodborne infections and the way they regarded their professional responsibility to provide care to these patients. We were able to identify that the majority of seniors had knowingly treated patients with one of these diseases, and believed that they had a professional obligation to do so. The study showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
0
5
1
2
Order By: Relevance
“…The level of willingness found in this survey was high when compared to previous reports of various groups' willingness to treat: 63.3 percent of Nigerian preclinical students, [15] 63.6 percent [16] and 78.4 percent [17]of Nigerian dentists, 62 percent of U.S. dental school seniors, [18] and is lesser than 84.3 percent of final year dental students in the United Kingdom [19], and 83 percent of U.S. dental students. [20] [21] .Willingness to treat is thought to be the most significant predictor of actual treatment of an HIV-positive patient.…”
Section: Discussion:-contrasting
confidence: 67%
“…The level of willingness found in this survey was high when compared to previous reports of various groups' willingness to treat: 63.3 percent of Nigerian preclinical students, [15] 63.6 percent [16] and 78.4 percent [17]of Nigerian dentists, 62 percent of U.S. dental school seniors, [18] and is lesser than 84.3 percent of final year dental students in the United Kingdom [19], and 83 percent of U.S. dental students. [20] [21] .Willingness to treat is thought to be the most significant predictor of actual treatment of an HIV-positive patient.…”
Section: Discussion:-contrasting
confidence: 67%
“…(49%), Azodo et al . (in which 58.8% expressed willingness to treat HIV positive individuals) and Solomon et al . (62%) among dental school seniors in the USA, but lower in comparison with the studies conducted by Utomi et al .…”
Section: Discussionmentioning
confidence: 78%
“…This is worrisome because it is expected that senior students should have greater knowledge and self‐confidence toward the treatment of these patients. Solomon et al17 reported that 80 percent of final‐year dental students in their study considered themselves competent to provide dental treatment to patients with HIV/AIDS. This additionally emphasizes the need for theoretical and practical education of dental students on this topic.…”
Section: Discussionmentioning
confidence: 95%